NEED ANALYSIS ON THE MATERIAL DEVELOPMENT OF TEACHING ESP SPEAKING - Fitria Lapele (Universitas Islam Negeri Alauddin Makassar, 2019)
University students must prepare themselves to be success in the global workforce. Hence, they should be able to speak English in the concerned fields of their specific major. In fact, speaking English for Specific Purpose (ESP) Students, especially students of non-English Language Education Department face some difficulties in constructing a good speaking. In this case, the ESP Speaking teacher should provide the good materials to help students master it easily. The teachers should consider using real life, authentic materials that reflect the target audience specialization. This study aimed to analyze the students’ needs on material development of ESP Speaking at University of Muhammadiyah Malang. It was intended to know the types of needs analysis conducted by the teachers for developing the materials. That is why; a narrative design was used to gather the research data. Besides, the instruments were interview guide and teachers’ documents. The result showed that: The teachers conducted four types of needs analysis for developing the materials, they areTarget Situation Analysis, Wants, Means, and Subjective Needs Analysis, Present Situation Analysis, and Lack Analysis. All the types the teachers have done in knowing students’ needs of ESP Speaking were generally in line with the requirements of good ways to develop ESP Speaking materials.